Pengembangan Sistem Presensi Online Berbasis Web Dengan Validasi Lokasi Menggunakan GPS dan Haversine Formula - Desi Anita; Rahmawati (CV. Multi Kreasi Media, 2025)
Effective employee attendance management is essential for improving productivity and human resource governance. PT. Bravo Sekuriti Indonesia still uses a manual attendance method through signatures on attendance forms, which is considered inefficient and prone to recording errors. This study develops a Web-Based Online Attendance System with location validation using GPS and the Haversine Algorithm to ensure that employees can only record attendance within a predetermined radius. The system is also equipped with online leave, permission, and sick-leave submission features with a digital approval workflow. The test results show that the system performs well, reduces data manipulation, and improves administrative efficiency. The System Usability Scale (SUS) score of 85.83 indicates that the system is easy to use and well accepted by users.